Importância do tratamento estético periodontal na reabilitação protética - Molon, Rafael Scaf [UNESP]; Avila, Erica Dorigatti de [UNESP]; Cirelli, Joni Augusto [UNESP]; Mollo Júnior, Francisco de Assis [UNESP]; Barros, Luiz Antônio Borelli [UNESP] (My University, 2011)
Gingival recession is a common deformity that affects a large number of people. This condition is frequently associated with esthetic complains and may lead to dental hypersensitivity. Thus, various surgical procedures have been proposed to provide root coverage. Since the 1950s, free and pedicle gingival grafts have been greatly used for treating gingival recession. However, after the 1985 Miller gingival recession classification, and with the development of other appropriated techniques that use subepithelial connective tissue grafts, gingival recession treatments have resulted in more predictable outcomes, especially with respect to Class I and II sites, i.e., in the absence of interproximal bone loss. This article reported the importance of aesthetical periodontal treatment in the prosthetic rehabilitation of a patient with a class I gingival recession with 3 mm of vertical extension in the superior canine. The treatment plan consisted of root coverage using subepithelial connective tissue graft (SCTG) associated with construction of new prosthesis.

A recessão gengival é uma deformidade comum que afeta um grande número de indivíduos e está frequentemente associada com comprometimento estético e com hipersensibilidade dentinária. Várias técnicas cirúrgicas têm sido propostas ao longo dos anos para lidar com este problema. Desde 1950, enxertos livres e enxertos gengivais pediculados têm sido bastante utilizados para o tratamento de recessão gengival. Contudo, com a classificação de Miller, proposta em 1985 e com o surgimento de outras técnicas utilizando enxerto de tecido conjuntivo subepitelial para recobrimento de raiz, os resultados se tornaram mais previsíveis, especialmente no que diz respeito a recessões Classe I e II, ou seja, na ausência de perda óssea interproximal. Este artigo relata a importância do tratamento estético periodontal na reabilitação protética de um paciente portador de recessão gengival Classe I de Miller com 3 mm de extensão vertical no canino superior direito. O plano de tratamento consistiu em recobrimento radicular utilizando enxerto de tecido conjuntivo subepitelial (SCTG) associado com deslocamento coronário do retalho e confecção de novas próteses.
Importance of aesthetic periodontal treatment on prosthetic rehabilitation: a case report
Keywords: Gingival recession; Connective tissue; Graft; Recessão gengival; Tecido conjuntivo; Enxerto